Spotlight on ORNAC Members: AN INTERVIEW WITH BARB SAWATSKY, RN - Harley, Catherine (Operating Room Nurses Association of Canada Journal, 2014)
Barb Sawastsky is a Perioperative Registered Nurse who has worked in the operating room setting since 1990. She is originally from St. Catharines but began her career at the Toronto General Hospital in Toronto, ON. In 1992 she returned to St. Catharines to work at the St. Catharines General Hospital which has since become part of the Niagara Health System (NHS). Over the years she has worked in the OR, in Recovery, and in the ICU. In the OR she has worked as a staff nurse, charge nurse, and in 2008 she became the Regional Educator for the NHS. She was involved in the planning of the OR, for a new hospital site, from 2006 to 2013. Barb is a member of ORNAC and the Perioperative Nurse Educators of Canada (PNEC). She is married with 2 children and enjoys spending time at her cottage on the French River.